Strategi Cuci Tangan Bersama dalam Menstimulasi Kesabaran Anak (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to describe the handwashing strategy in stimulating children's patience implemented at RA Ma'arif NU Plus 001 Samarinda. The social-emotional development of children aged 5-6 has been able to show tolerance and show empathy. Patience is a form of emotional expression that exists in every child, with patience will be able to control emotions, each child will be different in expressing his emotions, with the activities in washing hands together we will understand the values contained in hand washing activities together. This study used a descriptive qualitative approach, as for the data sources, namely teachers and kindergarten B children, and used data collection techniques including observation, interviews, and documentation. And using data analysis techniques, namely data condensation, data presentation, and conclusions. The results of this study show a joint handwashing strategy in stimulating children's patience through several activities, namely providing an understanding of good hand washing procedures before washing hands, then children are directed to queue, then children wash their hands using hand soap to make it cleaner, and after those wiping hands using a tissue so as not to be careless when wiping hands.